Alarm evaluation of an Intensive care unit Vital signs monitor system based in usability parameters (2017)
ABSTRACT: This article presents a test model for the usability of a vital signs monitoring system, specifically in Intensive Care Units (ICUs). This is because approximately 12% of annual failures occur in this area and 50% of these are due to usability problems. The model specifically measures the interaction between medical personnel with the equipment, beginning with a bibliographical review, then defining the equipment with which to work to later suggest and develop a protocol proposal which will enable evaluating its usability and thus suggest some changes to be implemented.